Autonomy and resilience in cultural work: looking beyond the 'creative industries'. Issue 2 (3rd April 2017) - Beirne, Martin; Jennings, Matt; Knight, Stephanie
Abstract: How do cultural workers deal with the tension between autonomy and control in their working lives? One answer, advanced in this journal by Mark Banks in 2010, is that cultural autonomy provides scope for self-realisation, and potentially for ways of working that challenge commercial and managerial constraints. It allows those with critical inclinations to resist unpalatable controls and initiate processes of struggle which may deliver improvements in the conduct and experience of work. More recent empirical studies have cast doubt on this interpretation, pointing to patterns of instrumental behaviour and conforming autonomy that reinforce earlier images of controlled or self-interested 'creatives'. With most of the relevant research focused on commercial contexts, this article considers whether publicly funded art provides more fertile terrain for the destabilising autonomy thesis. Four years of fieldwork with community arts practitioners in Scotland and Northern Ireland captures the everyday pressures of struggling to survive and to resist neoliberal cultural policies, managerial controls and fluctuating incomes. It also reveals collective capacities to intervene that are consistent with the Banks image of dissenting activists for change. The abiding impression at the end of the research is of grinding struggle rather than progressive change, however, or even sustained relief.